1978
DOI: 10.3168/jds.s0022-0302(78)83790-4
|View full text |Cite
|
Sign up to set email alerts
|

Minerals in Whey and Whey Fractions

Abstract: Liquid and dried acid and sweet wheys and the concentrates and permeates obtained from ultrafiltration of whey were analyzed for major and trace minerals. Calcium, magnesium, sodium, and potassium were determined by atomic absorption and phosphorus by a colorimetric method. Zinc, iron, copper, and manganese were determined by flameless atomic absorption. The composition of all wheys and their fractions differed in nutritionally important minerals. Calcium was three times as great and zinc twenty times as great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 6 publications
3
33
0
1
Order By: Relevance
“…Ash content had a high coefficient of variation (61.38 %), with a major difference between summer and the other seasons. Other academic studies have reported that the mineral composition of liquid acid whey is very close to that of sweet whey, except for higher levels of calcium and magnesium, which may be attributed to the method of casein precipitation (Alsaed et al 2013;Barana et al 2012;Wong et al 1978). As discussed by Jeličić et al (2008), the calcium content in acid whey is higher, due to its higher solubility at low values of pH.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Ash content had a high coefficient of variation (61.38 %), with a major difference between summer and the other seasons. Other academic studies have reported that the mineral composition of liquid acid whey is very close to that of sweet whey, except for higher levels of calcium and magnesium, which may be attributed to the method of casein precipitation (Alsaed et al 2013;Barana et al 2012;Wong et al 1978). As discussed by Jeličić et al (2008), the calcium content in acid whey is higher, due to its higher solubility at low values of pH.…”
Section: Resultsmentioning
confidence: 67%
“…This type of whey commonly contains higher levels of ash and lower levels of protein, when compared with sweet whey, and its food application is limited, due to its acid and salty taste (Baldissera et al 2011;Wong et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the activity of b-galactosidase from B. longum CCRC 15708 was enhanced by 9.8-and 12.0-fold, respectively, in the presence of 100 mM K + and Na + ( Table 2). In light of this property, application of b-galactosidase of B. longum CCRC 15708 will be more efficient and useful than enzymes from other sources in substrates such as milk, skim milk and whey, which contain substantial amounts of Na + and K + (Wong et al 1978;Flynn, 1992). Becker & Evans (1969) suggested that the association of monovalent cations with a b-galactosidase was on the basis of ionic radius, and that both K + and Na + ions affected the activity by inducing conformational changes in the enzyme structure.…”
Section: Carbohydratementioning
confidence: 98%
“…Among them are divalent (calcium, magnesium, zinc, iron, manganese, copper) and monovalent ions (sodium, potassium, chloride, phosphorus). During WPC manufacture most of minerals pass to the permeate, but still some of them (mainly Ca, Na, K, P) remain in retentate (Wong et al, 1978;Noël et al, 2008). These ions contribute to whey protein dispersion conductivity.…”
Section: Properties Of Wpc Dispersionsmentioning
confidence: 98%